419 Survival after minimally invasive surgery in early cervical cancer: is the uterine manipulator to blame?. (13th November 2020) - Nica, A; Kim, R; Gien, L; Covens, A; Bernardini, M; Bouchard-Fortier, G; Kupets, R; Hogen, L; Laframboise, S; May, T; Vicus, D; Ferguson, S
Abstract : Objectives: Minimally invasive radical hysterectomy (MIS-RH) has been associated with decreased survival in patients with early cervical cancer. The objective of this study was to determine whether the use of an intrauterine manipulator at the time of laparoscopic or robotic radical hysterectomy (RH) impacts patient outcomes. Methods: Retrospective study of all patients who underwent treatment of cervical cancer by MIS-RH at two large volume centres between 2006 and 2018. Results: A total of 224 patients were identified at the 2 centres; 115 had surgery with the use of an intrauterine manipulator, while 109 did not. Patients in whom a uterine manipulator was not used were more likely to have residual disease at hysterectomy (p<0.0001), positive lymphovascular space invasion (LVSI) (p=0.02), positive margins (0.0081), and positive lymph node metastasis (0.0029). Recurrence free survival (RFS) at 5 years was 80% in the no manipulator group and 94% in the manipulator group. After controlling for the presence of residual cancer at hysterectomy, tumor size (microscopic <7 mm or macroscopic ≥7 mm) and high-risk pathologic criteria (positive margins, parametria or lymph nodes), the use of a uterine manipulator was no longer significantly associated with RFS (HR=0.49, p=0.12). The only factor which was consistently associated with RFS was tumor size ≥7 mm (HR=9.5, p=0.03). Conclusion: The use of a uterine manipulator in patients with early cervical cancer treated with MIS-RH was not significantly associated with patients' risk of recurrence. We identified that the most significant predictor of cancer recurrence in this population was having a macroscopic tumor.